Ancient Theoretical Approaches to the Economy - Föllinger, Sabine (ΠΗΓΗ/FONS, 2024)
While earlier research looked at the question of ancient economic theories primarily from the perspective of a modern understanding of economics, more recent research has focused on understanding ancient economic theory from the perspective of its time. This article argues for the justification of both perspectives, because the interpretation of ancient texts allows for both and both can complement each other. For this, a careful and detailed reading of the ancient texts is important. This is why this article, by focusing on the 4th century BC, first distinguishes between different literary forms which offer us oeconomic reflections. These include explicit forms such as Plato’s Laws, Aristotle’s Politics and Xenophon’s Oikonomikos, but also implicit forms such as Hesiod’s Works and Days and Plato’s Republic. A careful interpretation of the texts makes it possible to recognize that ideas of economic regulation are the result of economic analyses to which they react, but which sometimes we can recognize only implicitly. So, we can find more as well as more diverse and more complex ancient theoretical approaches to the economy than had long been assumed in modern times. It can also be shown that the ancient world also knew the concept of homo oeconomicus and that a dichotomy between homo oeconomicus and homo politicus cannot be maintained. In a second step, this article presents categories of ancient economic thought in the form of a general overview. These include an anthropological perspective that views need as a basic human situation, as well as the awareness that economics is an area of human activity that can be controlled by means of regulations and incentives. Other important categories are household, trade, market and property. Considerations on the role of the state in economic processes also play a role.